PERAN SPIRITUALITAS KERJA TERHADAP MAKNA KERJA DAN KINERJA GURU DI PONDOK PESANTREN AULIA CENDEKIA PEKANBARU - Firmansyah Firmansyah; Fitri Juliani; Abdul Rahman; Lina Fitriana (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the effect of workplace spirituality on teacher performance, both directly and indirectly through meaningful work as a mediating variable among teachers at Aulia Cendekia Islamic Boarding School, Pekanbaru. The research employed a quantitative approach using a survey method. The population consisted of all teachers at the institution, with a total sample of 32 respondents selected through a census technique. Data were collected using questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS version 7.0. The results revealed that workplace spirituality had a positive and significant effect on meaningful work, with a path coefficient of 0.836 and a p-value of less than 0.001. However, workplace spirituality did not have a significant direct effect on teacher performance, with a path coefficient of -0.041 and a p-value of 0.407. Furthermore, meaningful work had a positive and significant effect on teacher performance, with a path coefficient of 0.874 and a p-value of less than 0.001. The indirect effect analysis indicated that meaningful work significantly mediated the relationship between workplace spirituality and teacher performance, with a coefficient of 0.731 and a p-value of less than 0.001. These findings suggest that workplace spirituality can improve teacher performance more effectively when it fosters a strong sense of meaningful work among teachers. Therefore, strengthening spiritual values and enhancing teachers’ perception of the meaningfulness of their profession are important factors in improving teacher performance within Islamic boarding school-based educational institutions